The pilgrimage to the Chapi sanctuary: a proposal for a religious touristic route in Arequipa - Málaga Núñez-Zeballos, Alejandro (2017)
In recent years, religious tourism has been on the rise around the world due to the significant economic benefits for the local population that result from such activity. This article describes and analyzes the large stand most important pilgrimage of the southern Andes, which is directed at an image of the Virgin Mary, called the Mamita de Chapi, located in a sanctuary 76 kilometers outside of the city of Arequipa, Peru. This work studies the origin, trajectory, and current status of the sanctuary and highlights important elements for creating the first religious touristic route in the region.